Synthesis of Efficient Oil-Soluble ZnAl2O4 Nanoparticles - Song, Xiaoyun; Chen, Qiang; Li, Wei; Zhang, Jun; Zheng, Shaohua (Asian Journal of Chemistry, 2012)
Oil-soluble spinel zinc aluminate (ZnAl2O4) nanoparticles with narrow size distribution were synthesized via a hydrothermal method and modified in situ by oleic acid. The nanoparticles have been characterized by means of scanning electron microscopy, infrared spectrum and powder X-ray diffraction. The dispersion stability of the ZnAl2O4 nanoparticles in lubricant oil has been measured by ultraviolet spectrophotometer. The results show that the modified nanoparticles are nearly monodisperse with good dispersion stability in lubricant oil. Due to the excellent disperse stability, the tribology performance of these modified ZnAl2O4 nanoparticles was also estimated and showed that they are promising for potential application as antifriction additives in lubricant oil.